(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The results of the complex research aimed at studying the effect of pre-harvest pruning on the formation of the coloring intensity of apple tree fruit in the conditions of the intensive orchard plantations in Kharkiv region were presented in the paper. The quality of a fruit appearance, in particular glow brightness and intensity, is an important factor in making the produce competitive, because it is the color that is the major criterion for a consumer’s choice. The purpose of the research was to estimate the efficiency of the application of canopy lighting pruning three weeks before fruit harvesting which was carried out to improve coloring and taste characteristics of the apples. The research was carried out in the production conditions of “Kharkiv fruit company” Ltd.; the cultivars of winter ripening terms, Pinova and Fuji, were studied. Pre-harvest pruning consisted in removing one-year-old and 20-cm long shoots to improve the fruit access to the light. It was found out that the improved lighting facilitated a more intensive warming of the fruit at the day time and their higher cooling at night, which in turn activated the anthocyanin synthesis, namely natural pigments, responsible for fruit red coloring. As a result, the number of the fruit with 75% surface coloring increased from 27% up to 93% for cultivar Pinova; the indicators for cultivar Fuji were from 14% up to 69%. In addition, the increase of sugar content in the fruit by 1.2 – 1.9% was recorded; it had a positive effect on their taste properties. The economic evaluation showed that the application of pre-harvest pruning enhanced the income by 37.2-52.2 th. UAH/ha, the profitability level increased by 8.6-12%, as compared with the control. Hence, pre-harvest crown pruning three weeks before harvesting is a highly effective technological technique which both improves decorative and commodity characters of the fruit and facilitates the enhancement of their taste value as well as the economic return of the intensive orchards. The results prove that it is expedient to introduce this method into business practice of the present-day horticulture.